WATER CLARIFICATION PROCESS AT THE TASHKENT TPP WATER TREATMENT PLANT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
the paper Describes an automated control and monitoring system for the regeneration of the n-cationite filter system, as well as operational monitoring of the Tashtpp water treatment plant.